Estimation of Growth Properties of Composite Entire Functions in Terms of their Minimum Modulus - Satendra Kumar , Majid Hamid Dar (Mathematical Statistician and Engineering Applications, 2022)
Recently many researchers have investigated the growth of entire functions of several complex variables with their corresponding left or right factor.An entire function of n complex variables for which order and lower order are same is said to be of regular growth.Further the functions which are not of regular growth is said to be of irregular growth.In this paper we will study growth properties of composite entire functions in terms of their minimum modulus by using the definitions of relative L-hyper order and relative L-hyper lower order of an entire function f with respect to an another entire function g.